(untitled) (Eurasian Journal of Philology Science and Education, 2018)
The article discusses the functions of adjectives in scientific-natural and scientific-technical texts. These functions were studied using the materials of the translation of scientific texts in Russian/English language system. The sentences and phrases with adjectives were classified by two criteria: the syntactic links of adjectives with other words; lexical and semantic peculiarities of adjectives playing the role of an attribute. According to these criteria the utterances with adjectives were divided into three groups: common utterances of a neutral adjective function; terminological phrases in which adjective is syntactically linked with terms; special utterances with adjectives being an emotional component. The methods of linguistic transformations of utterances were developed for a scientific text. According to these transformations neutral function is transforms into informative function. It is a linguistic technique which intensifies the degree of quality of an adjective by introducing adverb of an extent «very». The grammatical transformation of a sentence is the core of the second method. The third method is based on using stylistic technique of comparison. The informative function of an adjective in a scientific text is to evaluate objectively or express more precisely the essence of a scientific phenomenon expressed by a term. The informative function of an adjective is varied by lexical means and stylistic techniques.